Our Australian girl - Rippin, Sally (Puffin, 2013)
The Olympics are over, and everyone is feeling flat - including Lina. As she reads the newspaper every night with her father, Lina finds out that some of the Hungarian athletes have stayed behind and are hiding in Melbourne so they don't have to face the fighting in their homeland. Lina begins to suspect that one is being hidden by her cranky old neighbour, Mrs Bencszik. She writes an article about it and sends it to her hero, the Age journalist Stella Davis - who wants to meet her and publish the article! But Lina soon realises that Stella wants to steal the story for herself. Lina refuses to share the article, pretending instead that she made the whole thing up. But that doesn't mean that Lina's chance to be a real journalist is lost forever ... When she writes down her father's life story of how he fled Italy for fear of political persecution, her teacher secretly sends it to the newspaper. As Lina and her father settle down to read the paper together one evening, there it is. In this heartwarming conclusion to Lina's story, she comes to grips with her heritage and finally feels true pride in her family - and herself
Keywords: Geschichte 1900-2000; Girls / Juvenile fiction; Children's stories; Girls; Geschichte; Australia / History / 20th century / Juvenile fiction; Australia; Australien